The Impact of Employment Protection on the Industrial Wage Structure - John S. Heywood; Mary O'Mahony; W. Stanley Siebert; Ana Rincon-Aznar (Institute of Labor Economics (IZA), 2018)
This paper tests whether the job security offered by stricter employment protection legislation (EPL) undermines positive compensating wage differentials that would otherwise be paid. Specifically, we ask whether industries with relatively more need for layoffs and labour flexibility have lower wages in countries where stricter EPL protects workers from layoffs. We find this generally to be true for a large sample of industries in the major OECD countries over 1984-2005, particularly for wages of unskilled workers. However, we also find that where workers are well organised, they can take advantage of EPL to secure higher wages.
Keywords: I24; J31; J41; J50; J63; J83; K31; K51; L51; M50; 330; employment protection legislation; labour regulation; compensating wage differentials; education and inequality; labour organisation; layoffs